Morphometry and Meristic of Milkfish in Ponds Around Mangrove Wonorejo Surabaya - Larasati, Millenia Cantika Putri; Budijastuti, Widowati (LenteraBio : Berkala Ilmiah Biologi, 2022)
Morphometry and meristic are measurement certain parts of fish used to identify fish species. This study aims to analyze the relationship between morphometry and meristic of milkfish with environmental factors in ponds around Mangrove Wonorejo Surabaya. This research is an observational research to find the character relationship. The procedure in this study consisted of determining location, measuring environmental parameters, taking samples, identifying and measuring morphometric and meristics. Data analysis using SPSS 26 with Principal Componenet Analysis (PCA) technique. The environmental conditions have an average DO 9.27 mg/L, BOD 1.04 mg/L, pH 8.1, temperature 32.40C, salinity 20.3 ppt and obtained the milkfish species, namely Chanos chanos. The results of PCA on 21 morphometry and 6 meristics, most of which have a close relationship indicated by the value >0.50. The highest correlation value 0.998 in total length with pelvic fin length and weak correlation in length before the second dorsal fin and caudal peduncle length with 0,108. Close relationship related with function of pelvic fins for counterweight the position while swimming in stable state. The conclusion of this research is the increase in length of a morphometry character, meristic and good environmental conditions can affect the length growth of other characters.